Workspace design for crane cabins applying a combined traditional approach and the Taguchi method for design of experiments. Issue 2 (2nd April 2016) - Spasojević Brkić, Vesna K.; Veljković, Zorica A.; Golubović, Tamara; Brkić, Aleksandar Dj.; Kosić Šotić, Ivana
Abstract : Procedures in the development process of crane cabins are arbitrary and subjective. Since approximately 42% of incidents in the construction industry are linked to them, there is a need to collect fresh anthropometric data and provide additional recommendations for design. In this paper, dimensioning of the crane cabin interior space was carried out using a sample of 64 crane operators' anthropometric measurements, in the Republic of Serbia, by measuring workspace with 10 parameters using nine measured anthropometric data from each crane operator. This paper applies experiments run via full factorial designs using a combined traditional and Taguchi approach. The experiments indicated which design parameters are influenced by which anthropometric measurements and to what degree. The results are expected to be of use for crane cabin designers and should assist them to design a cabin that may lead to less strenuous sitting postures and fatigue for operators, thus improving safety and accident prevention.